2018
DOI: 10.1016/j.ijvsm.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic conditions of domestic owned rabbits in Osun State, southwestern Nigeria: Retrospective evaluation, risk factors and co-infestations

Abstract: Parasitism is of great concern to the production, reproduction and performance of man and animals. The present study evaluated the parasitic conditions of rabbits brought for medical attention in the major Veterinary hospitals in Osun State, Southwestern Nigeria during ten years (2006–2015). A total of 444 rabbits were brought during the study period, out of which 312 (70.27%) was diagnosed for mange, 126 (28.38%) for helminthoses, 60 (13.51%) for coccidiosis and 6 (1.35%) for flea infestation. There was no de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 9 publications
1
8
1
4
Order By: Relevance
“…In addition, the strength of infection intensifies mainly during the perinatal period and before weaning, which is associated with a considerable decrease in immunity. Older rabbits are typically carriers of coccidians [17,[21][22][23][24][25]. Similarly, Ilić et al [13] reported a greater extensity of coccidial infection in young rabbits (50.6%) than older ones (37.6%).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the strength of infection intensifies mainly during the perinatal period and before weaning, which is associated with a considerable decrease in immunity. Older rabbits are typically carriers of coccidians [17,[21][22][23][24][25]. Similarly, Ilić et al [13] reported a greater extensity of coccidial infection in young rabbits (50.6%) than older ones (37.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous publications indicate the distribution of invasive diseases of wild and domestic rabbits (Bordes et al, 2007;Sürsal et al, 2014;Okumu et al, 2014). It was proved that they can be infested by a number of parasites: helminths, protozoans and ectoparasites (Fernández-Aguilar et al, 2013;Ola-Fadunsin et al, 2018). According to Ilić et al (2018), infestation of rabbits with parasites in Serbia equaled 82.7%.…”
Section: Introductionmentioning
confidence: 99%
“…Also there was cellular and fatty degradation and infi ltration which is in confi rm with Singla's, et al [19] Al-Najjar, et al [20] and Aman D Moudgil, et al 2016 [21] observation. Their histopathological study of the affected liver showed the presence of fatty changes and infi ltration of mononuclear cells in the affected zones [19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%